2021
DOI: 10.5312/wjo.v12.i12.961
|View full text |Cite
|
Sign up to set email alerts
|

Far lateral lumbar disc herniation part 1: Imaging, neurophysiology and clinical features

Abstract: Far lateral lumbar disc herniations (FLLDH) represent a separate category of disc pathology which includes both intraforaminal and extraforaminal lumbar disc herniations, that are characterized by a peculiar clinical presentation, diagnostic and treatment modalities as compared to the more frequent median and paramedian disc hernias. Surgical treatment often represents the only effective weapon for the cure of this disease and over the years different approaches have been developed that can reach the region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Additionally, in a cadaveric study, it was found that drilling of the caudal TP, or in the case of L5-S1 FLDH the superior sacral ala, most easily exposed the exiting nerve root while also providing access to the disc without need for further boney removal [ 24 ]. In almost all cases, the extraforaminal disc fragment will be caudal to the exiting nerve root and displace it superiorly and laterally [ 5 ]. Thus, the caudal TP will be the most consistent boney landmark for accessing the extraforaminal disc.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, in a cadaveric study, it was found that drilling of the caudal TP, or in the case of L5-S1 FLDH the superior sacral ala, most easily exposed the exiting nerve root while also providing access to the disc without need for further boney removal [ 24 ]. In almost all cases, the extraforaminal disc fragment will be caudal to the exiting nerve root and displace it superiorly and laterally [ 5 ]. Thus, the caudal TP will be the most consistent boney landmark for accessing the extraforaminal disc.…”
Section: Discussionmentioning
confidence: 99%
“…Physical examination demonstrated a profound weakness of her right foot, including 3/5 strength of the tibialis anterior, an inability to heel walk, and a numbness along an L4 dermatome. Given the presence of a severe motor deficit in the subacute period and a strong desire to regain her foot strength, a joint decision made with the patient led to pursuing early surgery rather than engaging in additional non-operative treatment with epidural steroid injection and physical therapy [ 5 ]. The patient’s body mass index (BMI) was 25.5 kg/m 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 5 , 6 ] Due to its atypical imaging and insidious onset, FLDH is often misdiagnosed. [ 7 , 8 ] It can be mainly divided into foraminal type, extra-foraminal type and mixed type. [ 9 ] The prolapsed disc often compresses the exiting root and ganglion, leading to severe radicular pain.…”
Section: Introductionmentioning
confidence: 99%